Postoperative radial nerve palsy in humeral shaft nonunion reconstruction: Can the lateral paratricipital approach prevent this common complication?. Issue 10 (October 2022) - Gibbs, Christopher M.; Wawrose, Richard A.; Turvey, Blake R.; Moloney, Gele B.; Siska, Peter A.; Tarkin, Ivan S.
Highlights: Of those patients who underwent nonunion reconstruction of the humerus utilizing a lateral paratricipital approach, zero patients (0/16) developed a postoperative radial nerve palsy (RNP). Our overall rate of postoperative radial nerve palsy is consistent with the current literature; however, to our knowledge, our study is the first to include, analyze, and report the rate of postoperative RNP in regards to utilizing the lateral paratricipital approach when addressing nonunion reconstruction of the humerus. The data in our manuscript support the utilization of the lateral paratricipital approach as a surgeon controlled means of decreasing postoperative patient morbidity associated with postoperative RNP. Merits of this approach include triceps muscle preservation, radial nerve identification at the spiral groove, decompression of the nerve at the lateral intermuscular septum, and tension-free mobilization of the nerve for improved protection during manipulation and instrumentation. There was an increased rate of RNP with a longer duration of time between initial treatment and nonunion reconstruction with use of the triceps splitting approach. This suggests that it may be advisable to utilize a lateral paratricipital, rather than triceps splitting approach, if a posterior approach is required when treating a nonunion in cases where there is a greater period of time from initial treatment to nonunion reconstruction. Abstract: Background: Postoperative radial nerve palsy (RNP) is a well-known complication of nonunion reconstruction of the humerus. The purpose of the current study is to determine if the surgical approach for nonunion reconstruction of the humerus influences the rate of postoperative radial nerve palsy. Methods: A retrospective case-control study of all humeral shaft and extraarticular distal humerus nonunion reconstructions performed between January 1, 2004, and August 31, 2021, was conducted. Patients included were over 18 years of age, had a non-pathologic humerus fracture nonunion and had intact radial nerve function prior to nonunion reconstruction. Exclusion criteria consisted of nonunions involving the proximal humerus, intraarticular fractures, and reconstructive treatment procedures with either intramedullary nail or external fixation methods. Perioperative variables were recorded and analyzed in regard to the development of postoperative RNP. A subgroup analysis was performed to assess the interaction of significant variables on the development of postoperative RNP. Results: The overall rate of postoperative RNP in this series was 6/53 (11%). However, no cases of postoperative radial nerve palsy were observed in patients who underwent nonunion reconstruction with a lateral paratricipital approach. A new RNP was seen in 4/9 (44%) of those patients who underwent a triceps splitting approach, which was significantly higher than those utilizing either an anterolateral approach (2/28, 7%) or a lateral paratricipital approach (0/16, 0%, p = 0.007). Discussion and conclusion: Our data suggests that the lateral paratricipital exposure decreases the risk of radial nerve injury with nonunion reconstruction of the humerus. The lateral paratricipital exposure offers the benefit of radial nerve exploration, decompression, neurolysis and protection prior to fracture manipulation and instrumentation. This study shows conventional approaches may predispose patients to a high rate of postoperative RNP, similar to that in the literature.